2017
DOI: 10.1007/s11064-017-2205-0
|View full text |Cite
|
Sign up to set email alerts
|

Amphotericin B Increases Transglutaminase 2 Expression Associated with Upregulation of Endocytotic Activity in Mouse Microglial Cell Line BV-2

Abstract: Amphotericin B (AmB), a polyene antibiotic, is reported to cause the microglial activation to induce nitric oxide (NO) production and proinflammatory cytokines expression, and change neurotrophic factors expression in cultured microglia (Motoyoshi et al. in Neurochem Int 52:1290-1296, 2008). On the other hand, tissue-type transglutaminase (TG2) is involved in connection to phagocytes with apoptotic cells. Engulfment of neurons by activated microglia is thought to cause neurodegenerative diseases but detail is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Previously, it has been reported that an increase of TGM2 expression facilitates the generation of inducible nitric oxide synthase (iNOS), which might induce neuronal death [ 20 ]. Therefore, controlling TGM2 activity might provide an approach to protect neurons and care for CNS injuries [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been reported that an increase of TGM2 expression facilitates the generation of inducible nitric oxide synthase (iNOS), which might induce neuronal death [ 20 ]. Therefore, controlling TGM2 activity might provide an approach to protect neurons and care for CNS injuries [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, we reported in activated microglia that TG2 might be involved in endocytosis of fluorescent beads and dead cells, because of inhibition of the endocytosis by cystamine, an inhibitor of TG enzyme activity [39,40]. Cystamine also inhibited LPS-increased TG2 expression, iNOS expression, and NO production [39].…”
Section: Introductionmentioning
confidence: 92%
“…For example, NO downregulates endocytosis in rat liver endothelial cells ( Martinez et al, 1996 ) but promotes caveolae-mediated endocytosis as mentioned above ( Chen et al, 2018 ). Macrophages stimulated by the thymic peptide thyαl display enhanced NO levels as well as increased pinocytosis ( Shrivastava et al, 2004 ), as do amphotericin B-stimulated microglial cells ( Kawabe et al, 2017 ). Conversely, mouse peritoneal macrophages stimulated with activin A display both reduced NO and pinocytosis ( Zhou et al, 2009 ).…”
Section: Water Ions and Their Channels And Transporters In Pinocytosismentioning
confidence: 99%